1994
DOI: 10.7863/jum.1994.13.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transvaginal sonography with endometrial biopsy in asymptomatic postmenopausal women.

Abstract: The purpose of this study was to compare TVS with endometrial biopsy as a screening technique in asymptomatic postmenopausal women. Asymptomatic postmenopausal women were recruited by newspaper advertisement. Each study patient was subjected to pelvic examination and TVS followed by endometrial biopsy. Patients with suspected endometrial abnormalities by TVS (normal by endometrial biopsy) were evaluated further with hysteroscopy with biopsy or D&C or both. Eight patients were identified as having abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 3 publications
1
15
0
1
Order By: Relevance
“…Even among asymptomatic postmenopausal women, TVUS has been suggested to be a better screening tool than the more invasive endometrial biopsy [13]. However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Even among asymptomatic postmenopausal women, TVUS has been suggested to be a better screening tool than the more invasive endometrial biopsy [13]. However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies, 19,33,34,62,72,77 studies with selective histological sampling, 23,24,29,39,52,62,69 studies that reported results pooled for premenopausal and postmenopausal women, 42,71,84,97 and studies that measured endometrial thickness following tissue sampling 13,17,23,42,49,58,62 were excluded. In addition, studies that evaluated EVUS only in asymptomatic women, 16,35,67,69,81,93,98,99 women receiving tamoxifen, 31,32,51,56,59,75 and women with known endometrial cancer 43,58,100,101 ; studies not reporting endovaginal thickness measurements 15,26,52,71,72,74,76,77 ; and studies where the crude data could not be extracted 19,21,24,39,42,48,52,72,<...>…”
Section: Study Selectionmentioning
confidence: 99%
“…Recent studies indicate that D&C can identify 80% to 85% of cases of endometrial cancer, but other investigators have indicated a lower sensitivity. 20 However, D&C may miss many endometrial lesions, as it is performed blindly, and samples only a small portion of the total endometrial surface. In addition, pedunculated lesions can move away from the biopsy instrument, and incipient polyps may not be identified if the basal layer of the endometrium is not included in the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Despite numerous publications advocating the use of TVS and TVHS in evaluating women with postmenopausal bleeding, many physicians still consider endometrial biopsy (EMB) to be the standard of care when screening for endometrial diseases. 20 To address this issue, we prospectively performed 98 TVHS examinations one week before dilatation and curettage (D&C) operation in patients referred for PMB. All women with positive TVHS examination then underwent hysteroscopy or hysterectomy.…”
mentioning
confidence: 99%